2023
DOI: 10.1155/2023/2733232
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Prognostic Model for Predicting Colorectal Cancer Prognosis and Response to Immunotherapy Based on Cuproptosis-Associated lncRNAs

Abstract: Colorectal cancer (CRC) is a common and highly lethal gastrointestinal malignancy. Immunotherapy has shown positive efficacy in the treatment of CRC; however, only a minority of patients benefit from immunotherapy. The aim of this study is to construct a cuproptosis-related lncRNA (CRLs) risk score model to predict the prognosis and immune infiltration of CRC patients. Firstly, we synthetically analyzed 19 cuproptosis-related genes (CRGs) from CRC samples derived from the TCGA and obtained 33 CRLs that were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…There is other study that has also observed reduced tumorin ltrating CD8 + T cell values in SKCM patients [49]. This study's results on immune in ltration analysis align with those of Yang et al, who found decreased CD8 + T-cell in ltration of the high risk group in colorectal cancer patients [50].…”
Section: Discussionsupporting
confidence: 87%
“…There is other study that has also observed reduced tumorin ltrating CD8 + T cell values in SKCM patients [49]. This study's results on immune in ltration analysis align with those of Yang et al, who found decreased CD8 + T-cell in ltration of the high risk group in colorectal cancer patients [50].…”
Section: Discussionsupporting
confidence: 87%
“…A six SIGLEC family-related lncRNAs prognostic signature (AC007608.3, AC008750.1, AC039056.2, AC078788.1, AL021878.2, AL133279.1) was established to predict the OS of OC patients and all of them have close correction with worse prognosis of OC. Previous research has shown that AC007608.3 was related to cuproptosis and poor prognosis of colorectal cancer 23 . Feng et al 24 revealed that AC078788.1 was associated with tumor immunity and a favorable prognosis of OC.…”
Section: Discussionmentioning
confidence: 92%
“…We calculated the correlation coefficient between 15 SIGLEC family genes and lncRNAs based on Pearson correlation analysis. Then, SIGLEC family-related lncRNAs were selected out acrroding to the screening criteria p < 0.05 and |R|> 0.4 23 .…”
Section: Methodsmentioning
confidence: 99%